A Unified Data Model for ICH Online Inventories: A Proposal - Maria Teresa Artese; Isabella Gagliardi (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2020)
This paper proposes an investigation about problems arising when searching and managing Intangible Cultural Heritage data: how to find out which websites are dealing with them in the world, how to collect and evaluate web services provided to make integrated queries, how to model a common metadata structure able to collect ICH entities coming from different realities and provide them in Linked Open Data format. The study is based on the QueryLab prototype, an ongoing experimentation used to integrate different inventories to provide new and easy ways to query data.